Prevention of Early Marriage as an Effort To Overcome Stunting - Saputra, Nurman; Citami, Niko; Pamungkas Susani, Yoga; Ayu Eka Widiastuti, Ida; Suwita Sari, Putu Suwita Sari; Sulistya Affarah, Wahyu; Tirta Dirja, Bayu; Hagni Wardoyo, Eustachius (International Journal Of Community Service, 2024)
Early marriage is a significant social issue that can have a negative impact on the health and well-being of teenagers, and has the potential to exacerbate the problem of stunting among children. This activity aims to outline community service activities focused on preventing early marriage as a strategy to reduce the prevalence of stunting. One of the institutions that is expected to be a pioneer in implementing activities to prevent early marriage and overcome stunting in West Nusa Tenggara is the Faculty of Maritime Medicine, Mataram University. The activity is aimed at identifying risk factors for early marriage and their impact on the incidence of stunting. This activity was carried out by providing counseling, attended by 40 teenagers who were grade 9 students and 5 teachers at MTs Nurul Huda, Pijot Village, Keruak District, East Lombok Regency, West Nusa Tenggara Province. The results of this service activity show an increase in understanding regarding the risks of early marriage and stunting, as well as a change in attitudes towards education and health. In conclusion, efforts to prevent early marriage have proven effective in supporting efforts to overcome stunting, by having a significant impact on improving the health and welfare conditions of teenagers and children. It is hoped that this program can become a model for similar community service activities in the future. Keywords: Early marriage, stunting